The Impact of Public Expenditure on the Quality of Higher Education in Public Universities During the period 2000-2024 - Wafaa Issa; Manal Othman (Research Journal of Maaref University of Applied Sciences, 2026)
Educational institutions, especially public universities, are the main pillar of any sustainable development process, as they are responsible for graduating human competencies capable of driving the economy and society, and to ensure that these universities play their role to the fullest, the issue of funding becomes a pivotal issue, as public expenditure is the main source of support for the budgets of public universities. Economists agree that an adequate and effectively targeted level of spending is essential to achieving the quality of higher education. This can be measured by multiple indicators, including the quality of the curriculum and the efficiency of the faculty members, the modernity of the infrastructure and laboratories, the quality of scientific research outputs, and the alignment of graduates with the labor market. In Syria, public universities are increasingly challenging under the current economic conditions, putting significant pressure on available resources. In this context, the question of whether current public spending mechanisms can actually translate financial allocations into tangible improvements in the quality of higher education. Does the volume of spending itself improve quality? Or is the efficiency of allocating this expenditure the most important variable.